The Influence of The Glass Ceiling Phenomenon and Perceived Or-ganiztional Support on Employee Performance Mediated by Career De-velopment in The Regional Inspectorate of Pati Regency - Karina Kusumastuti Pratiwi; Tristiana Rijanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study explores how the Glass Ceiling and Perceived Organizational Support influence employee performance, with career development acting as a mediating variable. The research focuses on employees at the Regional Inspectorate of Pati Regency, utilizing a quantitative survey method involving 70 respondents. Data were analyzed using multiple linear regression. Results indicate that Glass Ceiling has a significant direct effect on performance, while Perceived Organizational Support does not. However, Career development played a mediating role between the Glass Ceiling and Perceived Organizational Support in relation to Employee Performance. These results offer practical insights for human resources management, particularly regarding Glass Ceiling, Perceived Organizational Support, Career Development and Performance.